Dynamics of a partially cavitating underwater vehicle - Semenenko, V.N.; Naumova, O.I. (Гідродинаміка і акустика, 2018)
The purpose of the paper is to analyze the peculiarities of the partially cavitating vehicle dynamics. The research method is a computer simulation using the approximation model of the unsteady supercavity basing on G. V. Logvinovich's principle of independence of supercavity's sections expansion. A method of determination of the balanced motion parameters for the partially cavitating vehicle is elaborated. The examples of computer simulation of the partially cavitating vehicle motion are given, incluing the vehicle speeding-up and deceleration. The longitudinal motion of the balanced partially cavitating vehicle is is shown to be statically unstable on depth. In this case, the motion stability loss occurs in "hard" non-oscillatory manner, unlike the supercavitation case. The methods of stabilizing the partially cavitating vehicle motion are proposed. The effect of cavity ventilation on the dynamics of the cavitating vehicle is studied. Целью работы является анализ особенностей динамики частично кавитирующих аппаратов. Метод исследования - компьютерное моделирование с использованием аппроксимационной модели нестационарной суперкаверны, основанной на принципе независимости расширения сечений каверны Г. В. Логвиновича. Разработан метод нахождения равновесных значений параметров движения частично кавитирующего аппарата. Приведены примеры компьютерного моделирования движения частично кавитирущего аппарата, в частности при его разгоне и торможении. Показано, что продольное движение сбалансированного частично кавитирующего аппарата статически неустойчиво по глубине. При этом потеря устойчивости движения, в отличие от случая суперкавитации, происходит "жестким" неколебательным образом. Предложены способы стабилизации движения частично кавитирующего аппарата. Исследовано влияние вентиляции каверны на динамику кавитирующего аппарата. Метою роботи є аналіз особливостей динаміки частково кавітуючих апаратів. Метод дослідження- комп'ютерне моделювання з використанням апроксимаційної моделі нестаціонарної суперкаверни, яка базується на принципі незалежності розширення перерізів каверни Г. В. Логвиновича. Розроблено метод знаходження рівноважних значень параметрів руху частково кавітуючого апарата. Наведено приклади комп'ютерного моделювання руху частково кавітуючого апарата, зокрема при його розгоні і гальмуванні. Показано, що поздовжній рух збалансованого частково кавітуючого апарата статично нестійкий по глибині. При цьому втрата стійкості руху, на відміну від випадку суперкавітації, відбувається "жорстким" неколивальним чином. Запропоновано способи стабілізації руху частково кавітуючого апарата. Досліджено вплив вентиляції каверни на динаміку кавітуючого апарата.